Inflation and Monetary Velocity in Latin America - Hanson, James S.; Vogel, Robert C. (The Review of Economics and Statistics, 1973)
CONTROVERSIES involving inflation, particularly inflation in developing countries, have usually focused on Latin America.1 One major point which emerges from these controversies is the distinction between a fully anticipated, fully adjusted inflation and an inflation which proceeds with such irregularity that economic agents are able neither to anticipate nor to adjust completely. To the extent that individuals can anticipate and adjust to inflation, a higher rate of inflation will cause the income velocity of money to rise, as attempts are made to exchange money for hedges against inflation.' The influence of inflation on monetary velocity is less clear, however, under the conditions of imperfect anticipation and adjustment which prevail in Latin America. Not only are the rates of inflation in most Latin American countries high, but they also tend to be highly variable. In addition, most Latin American countries have less than perfect markets for hedging against inflation, and these are further restricted by the regulations often imposed on interest rates, prices and international trade in the wake of inflationary conditions.' The present paper examines the impact of inflation on the income velocity of money for sixteen Latin American countries over the period 1950-1969. Such an examination not only indicates the sensitivity of demand for real cash balances to changes in the price level, but also reflects the extent to which economic agents under conditions prevailing in Latin America can anticipate inflation and adjust by hedging. Aside from Cagan's well-known work on hyperinflation (Friedman, 1956, pp. 25117), most empirical studies of the demand for money in individual countries conclude that inflation does not have a significant impact on velocity.4 These studies generally argue that the small changes in the price level usually observed cannot be adequately anticipated or are not large enough to cover the costs of adjustment. A recent article by Melitz and Correa (1970) on international differences in income velocity, like most studies of individual countries (but contrary to theoretical expectations), also concludes that inflation does not influence velocity. This article, like the present study, uses international comparisons, but the findings differ substantially. Melitz and Correa find that the coefficient for the impact of inflation on velocity does not have the expected sign and therefore omit the inflation variable from further consideration. They argue that price changes are important only in cases of hyperinflation and that adjusting to mild inflation is too costly and difficult to be worthwhile. Having excluded inflation as an explanatory variable, Melitz and Received for publication May 24, 1972. Revision accepted for publication January 30, 1973. * The authors wish to thank Michael C. Lovell for many helpful comments and suggestions, Francisco Chaves for assistance with data collection and computational work, and the Wesleyan Computer Center for generous use of its facilities. ' Best known is the monetarist-structuralist controversy over the causes of inflation and the impact of inflation on economic development. See, for example, Baer and Kerstenetzky (1964), Johnson (1967, pp. 281-291) and Baer (1967). 2-Johnson (1967, pp. 104-142) identifies the tax on real cash balances as the essence of the quantity theory approach to inflation, and it is the efforts to escape this tax which cause monetary velocity to rise with inflation. 'In discussions of inflation and economic growth, more costs and benefits of inflation are attributed to structural imperfections rather than to the tax on real cash balances. Structuralists emphasize the benefits of inflation in circumventing market imperfections, while monetarists focus on the costs of inflation in conjunction with inappropriate government regulations. See Johnson (1967, pp. 281-291) and Baer (1967). 4 However, some studies in a collection edited by Meiselman (1970) provide limited support for a positive influence of inflation on velocity in several less-developed countries. Deaver (Meiselman, 1970, pp. 7-67), finds the rate of inflation to be a significant variable in explaining velocity changes in Chile during the period 1932-1955, while Campbell (Meiselman, 1970, pp. 339-386) finds a positive correlation between velocity and changes in the rate of inflation in a comparative study of South Korea and Brazil. In a cross-country study Perlman (Meiselman, 1970, pp. 297337) finds nominal interest rates or inflation rates (as proxies for the opportunity cost of holding money) to be significant in explaining international differences in liquid asset portfolios.